ILRI's biometrics and research methods teaching resource launched in Addis Ababa - Rowlands, G.J. (2011)
John Rowlands, former Head of Biometrics at the International Livestock Research Institute introduces the second version of the 'biometrics' teaching resource. This version was 'launched' at ILRI Addis Ababa on 10 November 2011 as part of the 'Livestock Exchange' event. Supported by the Rockefeller Foundation and developed by staff from the University of Nairobi, University of Swaziland, University of Kwazulu-Natal, Islamic University of Uganda and ILRI, the resource contains case studies and teaching modules for use by lecturers, researchers and students in agriculture. The resource is online at: https://www.ilri.org/biometrics/default.htm